Effect of avocado/soybean unsaponifiables on ligature-induced bone loss and bone repair after ligature removal in rats - Oliveira, G. J. P. L. [UNESP]; Paula, L. G. F. [UNESP]; Souza, J. A. C. [UNESP]; Spin-Neto, R.; Stavropoulos, A.; Marcantonio, R. A. C. [UNESP] (Wiley-Blackwell, 2015)
The aim of this study was to evaluate the effects of administration of avocado/soybean unsaponifiable (ASU), a drug that is commonly used in the treatment of rheumatoid arthritis, on ligature-induced bone loss and bone repair after ligature removal in rats. Eighty-four rats were randomly assigned to four groups of equal size and received a daily gavage of either sterile saline [control (CTR)] or ASU (0.6 mg/kg), starting 7 d before (ASU/-7), on the day of (ASU/0) or 7 d after (ASU/+7) periodontitis induction. Periodontitis was induced by placing silk ligatures into the gingival sulcus of the second maxillary molars for 7 d; after 7 d, the ligatures were removed. Seven rats from each group were sacrificed, 7, 15 or 30 d after ligature removal. Bone resorption was evaluated by histomorphometry and micro-computed tomography (micro-CT). Immunohistochemistry was used to evaluate the expression of TRAP, RANKL and alkaline phosphatase (ALP), and quantitative PCR (qPCR) was used to evaluate the levels of interleukin-1beta (Il1β), tumor necrosis factor alpha (Tnfα), interleukin-6 (Il-6), Rankl and Alp. Statistical analysis was performed using the Shapiro-Wilk test, ANOVA and Tukey's test for normal data, and using the Kruskall-Wallis and Dunnet's tests for non-normal data (p < 0.05). Histomorphometry and micro-CT analysis showed greater bone resorption in the CTR group than in the ASU/0 (15 d) and ASU/+7 (7 and 15 d) groups. The CTR group also presented with a higher expression of TRAP (15 and 30 d) and RANKL (7 and 15 d) compared with ASU/0 and ASU/+7 groups. Similarly, qPCR analysis showed higher levels of Rankl and Il1β mRNAs, and lower levels of Alp mRNA, in the CTR group compared with all other groups (for all periods). ASU exhibited a positive effect on bone repair following ligature-induced periodontitis in rats.
Keywords: Animal studies; Avocado/soybean unsaponifiables; Host modulation; Periodontitis